Misi Dalam Konteks Pluralisme Agama Di Indonesia - Rumengan, Arthur Reinhard (Educatio Christi, 2020)
Until now, Church mission is still understood as assignment to go out and makeChristians of all nations. Many missionaries came to new region and try to change theirfaith and their civilization. This mission paradigm is not relevant anymore in pluralsociety and plural religion. Therefore, it is time for changing our mission paradimbecome inclusive and build dialog to each other. Dialog is important point to makegood relationship with other religions and of course, it is called mission. This researchaims to explore missions paradigm in Indonesia context through literature studymeanwhile observe the pluralism reality of Indonesia.